Multifunctional Magnetocontrollable Superwettable‐Microcilia Surface for Directional Droplet Manipulation. Issue 17 (15th July 2019) - Ben, Shuang; Zhou, Tiantian; Ma, Han; Yao, Jinjia; Ning, Yuzhen; Tian, Dongliang; Liu, Kesong; Jiang, Lei
Abstract: In nature, fluid manipulations are ubiquitous in organisms, and they are crucial for many of their vital activities. Therefore, this process has also attracted widescale research attention. However, despite significant advances in fluid transportation research over the past few decades, it is still hugely challenging to achieve efficient and nondestructive droplet transportation owing to contamination effects and controllability problems in liquid transportation applications. To this end, inspired by the motile microcilia of micro‐organisms, the superhydrophobicity of lotus leaves, the underwater superoleophobicity of filefish skin, and pigeons' migration behavior, a novel manipulation strategy is developed for droplets motion. Specifically, herein, a superwettable magnetic microcilia array surface with a structure that is switchable by an external magnetic field is constructed for droplet manipulation. It is found that under external magnetic fields, the superhydrophobic magnetic microcilia array surface can continuously and directionally manipulate the water droplets in air and that the underwater superoleophobic magnetic microcilia array surface can control the oil droplets underwater. This work demonstrates that the nondestructive droplet transportation mechanism can be used for liquid transportation, droplet reactions, and micropipeline transmission, thus opening up an avenue for practical applications of droplet manipulation using intelligent microstructure surfaces. Abstract : A bioinspired, multifunctional, and magnetocontrollable superwettable‐microcilia surface device to manipulate droplets is engineered and fabricated. Droplets can be continuously transported in a specified direction via a superwettable microcilia array surface whose structure can be switched between different states via an external magnetic field. Applications include nondestructive droplet transportation, drug delivery systems, droplet reactions, liquid transportation, and micropipeline transmission.